Comparison of Angiographic Characteristics of Peripheral Arterial Disease between Diabetic and Non-Diabetics - Ikram Ullah, Sami Ullah, Salman Ahmad, Mohammad Asghar Khan, Hikmat Ullah Jan (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Several factors contribute to the poor outcomes of peripheral arterial disease (PAD). The current study examined the results of peripheral transluminal angioplasty (PTA) in diabetics and non-diabetics with peripheral arterial disease (PAD). Patients and Methods: This cross-sectional study was carried out on 136 peripheral arteries disease patients including 84 non-diabetic and 52 diabetics in the department of Cardiology, Hayatabad Medical Complex, Peshawar during the period from January 2022 to June 2022. This study included patients with PADs who had PTAs performed on their femoral, iliac, infrapopliteal, and popliteal arteries. Study protocol was approved by the research and ethical committee. Patient’s demographic details and medical history were recorded. SPSS version 26 was used for data analysis. Results: The overall mean age was 64.6 ± 10.51 years. Diabetic patients were compared with non-diabetic patients in terms of age (63.8±11.2 versus 65.4± 9.82 years), smoking history (80.7% vs. 46.4%), hypercholesterolemia (25.4% versus 31.9%), and ischemic heart disease (40.6% versus 36.5%). The frequency of hypertensive patients was higher 64.8% in diabetic patients against 40.6% in non-diabetic patients. In terms of arterial segment below the knee and profunda femoris, arterial disease had higher severity in diabetic patients. Diabetic patients were more susceptible to amputation (43.2% vs. 12%, OR=4.8, P=0.001) and had higher mortality (48.9% versus 23.8%). Conclusion: The present study found that higher prevalence of limb ischemia, amputation, and higher rates of restenosis following peripheral transluminal angioplasty was found in diabetic patients compared to non-diabetic patients. Diabetic patients had poor prognosis and worse arterial disease than non-diabetic patients. Keywords: Diabetic patients, Angiographic characteristics, Peripheral arteries disease.